Three phase inverter for induction motor by using pi-repetitive controller with arduino - Hussin, Mohd Najib (2014)
The proportional integral (PI) repetitive controller that is applied to the three phase inverter for the three phase induction motor is developed. This project is about to design a combination of PI-Repetitive controller simulation and fabricating the hardware to control the speed of a three phase induction motor. The controller eliminates the periodic errors on the output current due to inverter current nonlinearity and load disturbances. The controller is implemented on a gate driver, three phase inverter and filter prototypes which are constructed in laboratory. Open-loop and closed-loop condition are verified by means of simulation and experiments in order to investigate the stability of controller. The result of the controller’s performance between simulation and hardware are explained in this report in terms of the PWM output and three phase inverter output waveform. The PI-Repetitive controller will solve the starting problem of the three phase induction motor and minimizes the line current error to maintain the required steady state condition.